2015
DOI: 10.1016/j.celrep.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 Promotes Colorectal Carcinogenesis by Enhancing Polymorphonuclear Myeloid-Derived Suppressor Cell Population and Function

Abstract: Summary Our study reveals a non-canonical role for CCL2 in modulating non-macrophage, myeloid-derived suppressor cells (MDSCs) and shaping a tumor-permissive microenvironment during colon cancer development. We found that intratumoral CCL2 levels increased in patients with colitis-associated colorectal cancer (CRC), adenocarcinomas, and adenomas. Deletion of CCL2 blocked progression from dysplasia to adenocarcinoma and reduced the number of colonic MDSCs in a spontaneous mouse model of colitis-associated CRC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
259
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(283 citation statements)
references
References 63 publications
9
259
0
Order By: Relevance
“…CCL2 could mediate recruitment of MDSCs to tumors and promote the function of MDSCs via STAT3 pathway. 44 And chemokine CXCL1, activated by IL-6, is also responsible for MDSCs accumulation. 45 Also, CCL2 and CXCL1 regulate the polarization of M1 macrophages to M2 phenotype and the recruitment of TAMs to tumor microenvironment.…”
Section: And Cd11bmentioning
confidence: 99%
“…CCL2 could mediate recruitment of MDSCs to tumors and promote the function of MDSCs via STAT3 pathway. 44 And chemokine CXCL1, activated by IL-6, is also responsible for MDSCs accumulation. 45 Also, CCL2 and CXCL1 regulate the polarization of M1 macrophages to M2 phenotype and the recruitment of TAMs to tumor microenvironment.…”
Section: And Cd11bmentioning
confidence: 99%
“…We found that stimulation of TLR7 expressed by adenocarcinoma cells modulated the immune infiltrate, leading to a significant expansion in MDSCs, associated with an increased secretion of CCL2 and GM-CSF in the tumor microenvironment. Both these cytokines are known to play a key role in the recruitment of MDSCs 38,41,42 . Indeed, the absence of CCL2 production by cancer cells considerably reduces the recruitment of MDSCs into tumors 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Both these cytokines are known to play a key role in the recruitment of MDSCs 38,41,42 . Indeed, the absence of CCL2 production by cancer cells considerably reduces the recruitment of MDSCs into tumors 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Constitutive deletion or antibody-mediated neutralization of CCL2 halts neoplastic progression in an inflammationassociated tumor model. 20,29 Interleukin-17 is a pro-inflammatory cytokine that is thought to promote neutrophil chemotaxis and degranulation, and increased expression of IL-17 has been shown in cancer cells and TAMs, suggesting it may play an important role in the regulation of the tumor microenvironment. Previous studies have suggested a causal relationship between IL-17 production and the level of circulating MDSC.…”
Section: Discussionmentioning
confidence: 99%